Potential health risks of waste pickers - Manuelle Carvalho Cardozo; Ramon Missias Moreira (O Mundo da Saúde)
Waste pickers have an important role in contributing to the growth and development environment. Analyzing their per- ceptions on issues that relate to health is necessary since their representations determine positive or negative attitudes against their health and quality of life. The study aimed to analyze risk factors related to the health of waste pickers. This is a qualitative study, descriptive and exploratory, conducted in 2013 with 10 pickers, of both genders, in a cooperative in Jequié-BA. Data were generated through semi-structured interviews and analyzed using the technique of Thematic Content Analysis Categorical. Emerged three categories: perception of recyclable material collectors on the disease process, percep- tions about work accidents, and health risks related to their activity. Results indicate that collectors perceive health as a necessary tool to get work as a requirement to generate livelihood. In the exercise of the activity there was noted physical risks, chemical, biological, ergonomic, and work accident. The risks were seen as a condition of return for subsistence. Public policies in education and health need to be reviewed and appropriate to the reality of this population, influencing the management of their health care.